Análise de propostas de produção de textos orais em livros didáticos do ensino médio - Lorenna Bolsanello de Carvalho (2014)
The current educational guidance to the formation of students who can use the Portuguese Language with sureness in different contexts put the text as a fundamental tool to the linguistic education. It considers extremely necessary the work with text comprehension and text production in classes, with special attention to the public contexts of language usage. The main objective of this investigation is to analyse the activities of oral production in Portuguese Language student textbooks produced to High School, in a way to comprehend if the activities of oral production can contribute to the formation of proficient students, capable of expressing their ideas in public and formal contexts. This research presents as bibliographic reference the discursive vision of the Textual Linguistics, according to which the language is observed as a social activity not forgetting the structural and mental aspects inherent to it -, that needs to be analysed in relation to the social and historical contexts existent during the communication. The studies of Marcuschi (2001, 2008, 2010), Koch (2009), Dolz e Schneuwly (2004) were used as theoretical reference to this work. The corpus of this research is formed by three collections of books made to High School Brazilian degree and approved by the National Programme of School Textbooks (PNLD). As main result, we observed that the books begin a systematic teaching of the oral production based in the category of Textual Genres. The usage of the Textual Genres to guide the production of the oral texts shows that the books have an interactive and discursive perspective to the concepts of Language and Text. However, some few times residues of the dichotomy vision of the Oral-Literacy relation phenomenon can be found on the books.